The reality of virtual reality - Schöne, Benjamin; Kisker, Joanna; Lange, Leon; Gruber, Thomas; Sylvester, Sophia; Osinsky, Roman (Frontiers in Psychology, 2023)
Virtual reality (VR) has become a popular tool for investigating human behavior and brain functions. Nevertheless, it is unclear whether VR constitutes an actual form of reality or is more like an advanced simulation. Determining the nature of VR has been mostly achieved by self-reported presence measurements, defined as the feeling of being submerged in the experience. However, subjective measurements might be prone to bias and, most importantly, do not allow for a comparison with real-life experiences. Here we show that real-life and VR height exposures by means of 3D-360° videos are mostly indistinguishable on a psychophysiological level (EEG, HRV), while both differ from a conventional 2D laboratory setting. Using a fire-truck, three groups of participants experienced either a real-life (N=25), a virtual (N=24) or a 2D-laboratory (N=25) height exposure. Behavioral and psychophysiological results suggest that identical exogenous and endogenous cognitive as well as emotional mechanisms are deployed to process the real-life and the virtual experience. Specifically, alpha- and theta-band oscillations in line with heart-rate variability, indexing vigilance and anxiety, were barely indistinguishable between those two conditions, while they differed significantly from the laboratory setup. Sensory processing, as reflected by beta-band oscillations, exhibits a different pattern for all conditions, indicating further room for improving VR on a haptic level. In conclusion, the study shows that contemporary photorealistic VR setups are technologically capable of mimicking reality, thus paving the way for the investigation of real-world cognitive and emotional processes under controlled laboratory conditions. For a video summary please see https://youtu.be/fPIrIajpfiA